Biodecolorization of Reactive Red 120 azo dye by metal-ion-tolerant Lysinibacillus capsici and its potential application in textile effluent treatment - Kusumlata,; Singh, Rajat Pratap; Ambade, Balram; Kumar, Ashish (Frontiers in Environmental Science, 2025)
Currently, the textile industry is among the most rapidly expanding areas of the economy and is an important source of water pollution. There are many efficient chemical and physical methods for treating textile effluents, but they produce secondary pollutants. Therefore, there is a need to manage textile wastewater. The potential Lysinibacillus capsici bacterial strain has been isolated from the bark borer insect tunnel of the Peltophorum pterocarpum plant and has been determined to be effective in >95% decolorization of Reactive Red 120 (RR120) and other azo dyes, such as AB-113 (85%), orange II (94.62%), Congo red (94.62%), phenol red (94.54%), and mixtures of azo dyes (81.66%). Physico-chemical factors were optimized manually, including Taguchi design. Fabric discolorations by L. capsici was qualitatively studied. FT-IR, GC–MS, and UV absorbance studies also confirmed that the dye had been broken down into its amines. Research findings using enzyme assays have shown that the bacteria Lysinibacillus capsici can utilize laccase and manganese peroxidase and are capable of degrading dyes significantly. According to this work, immobilized L. capsici cells and the studied four bacterial consortia, namely, Lysinibacillus capsici, Alcaligenes faecalis subsp. phenolicus, Acinetobacter baumannii, and Pseudomonas aeruginosa, may be used to degrade RR120 effectively, and it is concluded that L. capsici is significantly efficient in textile effluent treatment.